ڕۆلێ مەسیحییان یێ شارستانی ل ژێر سیبەرا دەولەتا ئێلخانی (٦٥٦-٧٣٦ك/١٢٥٨-١٣٣٥ز) ڤەکۆلینا موستەل ژ دکتورناما (مەسیحی ل ژێر سیبەرا دەولەتا ئێخانی ٦٥٦-٧٣٦ك/١٢٥٨-١٣٣٥ز) خواندنەکا مێژوویی - شرۆڤەکاری - MIRZO, FALAH KHAIRI; ISMAIL, FARSAT MERIE (Journal of Duhok University, 2023)
After the Mongols attacked the Islamic world, they were able to control a wide geographical area, where they met different civilizations, so they tried to create a bridge to communicate with the owners of those civilizations, so they benefited from the cultural output of those nations and at various levels, such as applied sciences, humanities, reconstruction, and agriculture. As well as industry, and because of the sympathy of the Mongol khans and their wives with Christians in that time period, many Christian scholars appeared and contributed to their civilizing role. The research attempted to answer a set of important questions, including: At what stage of the rule of the Ilkhanate state were Christians able to contribute to the civilized construction? What are the scientific fields in which Christian scholars contributed? Who are the most prominent Christian scholars? What are the Christian sects that had the most prominent role in these sciences?